MANFAAT HASIL PELATIHAN TATA RIAS PENGANTIN SUNDA PUTERI SEBAGAI KESIAPAN UJI KOMPETENSI RIAS PENGANTIN - Nova Kristiana; Marlina Marlina (Universitas Pendidikan Indonesia, 2016)
The study examines the benefits of Sunda Puteri bridal makeup training results as a competency test readiness of bridal makeup conducted by YUYU Courses and Training Institute in Bandung. The method used in this research is descriptive analytic method with data collection using questionnaire. The research sample using the total sample, courses and training institution’s learners who have passed the training of Sunda Puteri bridal subject, force in 2013 which amounted to 30 peoples. The results showed that more than half of the learners know the characteristics and tools Sunda Puteri bridal makeup, less than half of the learners know the Sunda Puteri bride's face shape design, half of the learners know the Sunda Puteri bridal accessories, more than half of the learners know the Sunda Puteri ronce flowers and wedding dress as the readiness of the top bridal competency test. The conclusions of the study indicate that the majority of people who learn Sunda Puteri bridal makeup program force in 2013 have benefited from the training results as a competency test readiness of bridal makeup.